2020
DOI: 10.1186/s41938-020-00226-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between biological and chemical control programs of certain sweet pepper pests in greenhouses

Abstract: Sweet pepper is an important vegetable crop in Egypt. It is cultivated for local consumption and exportation. The crop is attacked by a large number of pest species such as Western flower thrips, Frankliniella occidentalis (Pergande), whitefly, Bemisia tabaci (Genn.), the two-spotted spider mite, Tetranychu surticae Koch, and the beet armyworm, Spodoptera exigua (Hubner). The present study was conducted on the sweet pepper cultivated in greenhouses, during the winter plantation 2016/17 in a commercial farm loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…These results are in agreement with previous investigations, which showed that inoculation of green pepper seeds with B. amyloliquefaciens bacteria caused an increase in vitamin C, total phenols and antioxidant activity (Cisternas-Jamet et al, 2020). The results of another study showed that the use of biological agents could lead to a higher yield of sweet pepper (El Arnaouty et al, 2020). Higher concentration of micronutrients such as Fe, Mn, Zn and Cu can increase the antioxidant activity within plant tissues as these essential elements are cofactors of enzymatic antioxidants such as superoxide dismutase.…”
Section: E Ect Of Biological and Chemical Treatments On The Total Phe...supporting
confidence: 93%
“…These results are in agreement with previous investigations, which showed that inoculation of green pepper seeds with B. amyloliquefaciens bacteria caused an increase in vitamin C, total phenols and antioxidant activity (Cisternas-Jamet et al, 2020). The results of another study showed that the use of biological agents could lead to a higher yield of sweet pepper (El Arnaouty et al, 2020). Higher concentration of micronutrients such as Fe, Mn, Zn and Cu can increase the antioxidant activity within plant tissues as these essential elements are cofactors of enzymatic antioxidants such as superoxide dismutase.…”
Section: E Ect Of Biological and Chemical Treatments On The Total Phe...supporting
confidence: 93%
“…Management strategies of greenhouse pests using chemicals were reported to result in several problems, such developments of resistance to chemicals by pests, and environmental and health problems are caused by those chemical pesticides [17]. The possibility of applying biological control programs to problems of greenhouse pests is highly recommended.…”
Section: Pest Managementmentioning
confidence: 99%
“…Biological control strategy such as releasing different predators and parasitoids was reported to be environmentally friendly production method of sweet pepper. Applying the biological control program resulted in a high yield of sweet pepper production (35.06%) compared with the control [17]. In this book chapter, various pest control methods are reviewed.…”
Section: Pest Managementmentioning
confidence: 99%
“…Controlling greenhouse pests by chemical pesticides results with many problems, such as development of resistance in pests and rising environmental and health concerns (Arnaouty et al, 2020). Indeed, greenhouse crops are harvested frequently, at short intervals, and thus intensive use of chemicals becomes questionable because of the possible contamination of products with chemical residues.…”
Section: Introductionmentioning
confidence: 99%
“…They will not completely eliminate pest problems but can reduce pest population, and damage to an acceptable level (under the economical threshold). Biological control generally requires more time than pesticides to bring a pest population under an acceptable control level (Arnaouty et al, 2020).…”
Section: Introductionmentioning
confidence: 99%